Human Papillomavirus Prevalence and Genotype Distribution in Cervical Swab Samples in Istanbul, Turkey - Sema Alacam; Ayfer Bakir (Journal of Infection in Developing Countries)
Introduction: Human papillomavirus (HPV) is the most common sexually transmitted infection agent worldwide and, with high-risk (HR) HPV genotypes, is the main factor for development of cervical cancer. This study aimed to assess the prevalence of HPV and distribution of HR-HPV genotypes in cervical swab samples and compare them with demographic and clinical data.